The awareness of lean manufacturing implemented practices in SME in Sabah State: TQM And TPM practices approach - Mohd Adzrie Radzali; M A S M Armi (IOP Publishing Ltd, 2021)
This study aims to evaluate the awareness of implemented practices that already applied and the implementation of lean manufacturing practice of Total Quality Management (TQM) and Total Productive Maintenance (TPM) on Small Medium Enterprise (SME) companies in Sabah. Regarding the implementation of TQM and TPM practices of lean manufacturing, this study evaluates the awareness implementation of lean manufacturing practices TQM and TPM among manufacturing company located in Sabah before analyzing the respondent survey data. As to know better the awareness of TQM and TPM practices, a study of the awareness of lean manufacturing implemented practices was conducted which to identify the practices that already been implement and the pillars practices that highly and lowest implemented to the SME’s companies in term of TQM and TPM practices. The scope of this study has covered the manufacturing company of drinking manufacturing industry that is actively operating in Sabah, specifically on Small Medium Enterprise (SME) companies. The methodology used for the study was by survey questionnaire which contains open and closed ended questions, sent out to desired respondents. The outcomes of the analysed data were created using descriptive statistics by explaining the trends in dataset and Cronbach’s Alpha to test the internal reliability of the item. This study finds significant evident of the implementation of lean manufacturing and its practices among SME’s drinking manufacturing companies in Sabah, as well as the awareness implementation of lean manufacturing practices with a statistical value.